Blue whiting (Micromesistius poutassou) sex ratio, size distribution and condition patterns off Portugal - Gonçalves, Patrícia (2019)
The sex ratio is an important trait of natural populations and a key parameter for assessing the reproductive potential and stock status of exploited fish populations. In fisheries research, knowledge on spatial and temporal sex ratio variation can inform on the capacity of a population to support exploitation and environmental changes. Blue whiting (Micromesistius poutassou) shows sexual growth dimorphism after maturation, with females achieving greater lengths than males. The main goal of this work was to investigate seasonal patterns in the blue whiting sex distribution, size structure and condition in three areas along the Portuguese coast (north, southwest and south), based on bottom trawl surveys performed in autumn and winter between 1998 and 2015. Smaller blue whiting (12–24 cm) were found in shallow areas down to 250–300 m while larger individuals (>24 cm) were spread deeper down to 400–500 m. Condition factor Fulton K differed significantly between seasons in all the areas (F = 11.72; p-value <0.001) and between sexes (F = 6.14; p-value <0.05). The proportion of females changed between autumn and winter (χ2(1) = 4.38, p = 0.03) and across depths (χ2(1) = 4.73, p = 0.03). Thus, this study revealed seasonal and depth variations in the blue whiting sex ratio along the Portuguese coast.